Ten-Years Cardiovascular Disease Risk Assessment among Health Camp Attendees - Khatri, Pratima; Regmi, Bhawana; Sayami, Jamuna Tamrakar (Journal of Institute of Medicine Nepal, 2025)
Introduction: Cardiovascular disease burden has been increasing globally. The risk was greater in low-middle-income countries than in developed countries. The objective of the study was to assess the ten years of cardiovascular disease risk among the health camp attendees. Methods: Physiometric measurement of the 159 health camp attendees was used as data. The major variables were height, weight, systolic blood pressure, gender, and smoking. Likewise, a WHO non-laboratory-based risk chart was used to identify the cardiovascular risk among the attendees. The non-laboratory-based CVD risk chart categorized the participants into 5 risk groups: very low (<5%), low (5% to <10%), moderate (10% to <20%), high (20% to <30%) and very high (≥30%) risk. Results: The mean age (SD) of the participants was 45.64 (±13.97) ranging from 19 to 82 years. The majority of participants 62.3% were female, 58.5%, and 12.6% were smokers. The mean systolic BP (SD) was 121.84 (±19.3) mmHg ranging from 90 to 200, among this 62.9% of participants had less than 120 mmHg. Similarly, the mean body mass index (SD) was 25.3 (±5.1) ranging from 16.6 to 38.8, out of this 42.8% had a body mass index of 20-24. Regarding the ten years CVD risk of participants, the majority (76.1%) had very low CVD risk followed by 14.5% low risk, and 9.4% had a moderate risk. There was no high and very high CVD risk found among participants. Ten year CVD risk had strong positive relation (r=0.795) with age and a moderated positive relation (r= 0.519) with systolic BP at 0.01 level of significance. Conclusion: CVD risk was lower among the health camp attendees who were female, non-smoker, systolic BP <140, and normal body mass index. Therefore, priority should be given to those who practice unhealthy behavior and abnormal SBP and BMI.